can some one check this for me?

solving...

4x = 4-5(x+2)

Reorder the terms:

4x = 4 + -5(2 + x)

4x = 4 + (2 * -5 + x * -5)

4x = 4 + (-10 + -5x)

Combine like terms: 4 + -10 = -6

4x = -6 + -5x

Solving

4x = -6 + -5x

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.

4x + 5x = -6 + -5x + 5x

Combine like terms: 4x + 5x = 9x

9x = -6 + -5x + 5x

Combine like terms: -5x + 5x = 0

9x = -6 + 0

9x = -6

Divide each side by '9'.

x = -0.6666666667

Simplifying

x = -0.6666666667I dont think that is right is it?

I make it x= 2